Electrochemical Solid-State Electrolyte Reactors: Configurations, Applications, and Future Prospects - Li, Weisong; Zhai, Yanjie; Gong, Shanhe; Zhou, Yingying; Xia, Qing; Wu, Jie; Zhang, Xiao (Nano-Micro Letters, 2025)
The advancement of clean electricity is positioning electrochemical reactors at the forefront of future electrosynthesis technologies. Solid-state electrolyte (SSE) reactors emerge for their distinctive configurations and ability to produce high-purity fuels and chemicals efficiently without additional purification steps. This marks a substantial development in electrochemical synthesis. In this perspective, we critically examine cutting-edge innovations in SSE devices with particular emphasis on the architectural introduction of core cell components, novel electrochemical cell configurations, and assembly methodologies. The use of SSE reactors is presently undergoing a pivotal transition from fundamental laboratory investigations to large-scale engineering implementations, demonstrating remarkable progress in multiple domains: (1) sustainable synthesis of high-value organic acids (formic and acetic acids), (2) production of critical oxidizers hydrogen peroxide (H2O2) and liquid fuels (ethanol), (3) ammonia (NH3) production, (4) carbon capture technologies, (5) lithium recovery and recycling, and (6) tandem or coupling strategies for high-value-added products. Importantly, the transformative potential in environmental remediation, particularly for airborne pollutant sequestration and advanced wastewater purification, is addressed. Additionally, the innovative architectural blueprints for next-generation SSE stack are presented, aiming to establish a comprehensive framework to guide the transition from laboratory-scale innovation to industrial-scale deployment of SSE devices in the foreseeable future. Highlights: 1 Solid-state electrolyte reactors are elucidated in terms of their distinctive electrochemical architecture to facilitate the efficient direct synthesis of fuels and chemicals without the need for traditional purification steps. 2 The core components, variable configurations, and distinct electrochemical reaction mechanisms of different chambers are systematically summarized. 3 Potential future application scenarios and advanced cell stack designs are pointed out.